Surface-modified PVDF membranes for separation of dye by forward osmosis - Muratow, Marta; Yalcinkaya, Fatma; Bryjak, Marek; Siekierka, Anna (Frontiers in Membrane Science and Technology, 2024)
Modification of membranes is widely used for altering their separation properties. In this study, the modification of PVDF nanofiber mat by deposition of polyamide layers was evaluated to improve dye recovery by means of forward osmosis process. The polyamide active layer was prepared by a reaction of cyclic aromatic amines, m-phenylenediamine, or piperazine, and trimesoylchloride. The modification progress was monitored by FTIR analysis, water uptake, nitrogen content, and grafting yields. Investigated membranes showed an excellent dye separation features with water flux and dye fluxes strongly related to type of applied amines and reaction time. The best obtained membrane demonstrated outstanding performance in forward osmosis; their water flux was 3.3 LMH and rejection rate of 97% for bromocresol green dye. The membrane allowed increase dye concentration by 50% after 24 h of the process.